An atypical case of hepatic cavernous hemangioma - Brogna, Alfio (BioMed Central, 2009)
INTRODUCTION: The case of an atypical hepatic angiocavernoma is referred. The lesion, first described as a hypoechogenic area compared to the surrounding parenchyma, with anechogenic shoots inside, suggestive for vascular structures developed one year later into a totally asonic area with frayed margins. This change is very unusual and uncommon for this kind of lesions. CASE PRESENTATION: The case of a 74-year old caucasian male, complaining of slight dyspeptic symptoms (post-prandial fullness and bloating) is referred. The routine blood tests were all normal. Abdominal ultrasound showed a large, roughly round-shaped lesion (diameter 14 cm) in the VIII hepatic segment diagnosed as hepatic angiocavernoma, which turned unexpectedly in a cystic like lesion one year later. CONCLUSION: The atypical angioma's degeneration could account for one of the causes of the patient's exitus. It could be related to blood seizure by the large hepatic angioma due to the intratumoural haemorrhage.